Atomic resolution structure of a chimeric DNA–RNA Z‐type duplex in complex with Ba2+ ions: a case of complicated multi‐domain twinning. Issue 2 (4th February 2016) - Gilski, Miroslaw; Drozdzal, Pawel; Kierzek, Ryszard; Jaskolski, Mariusz
Abstract : The self‐complementary dCrGdCrGdCrG hexanucleotide with not only alternating pyrimidine/purine bases but also ribo/deoxy sugars crystallized in the presence of barium cations in the form of a left‐handed Z‐type duplex. While the structure has monoclinic symmetry, the crystals show complicated twinning, with the diffraction pattern arranged on a hexagonal lattice. Abstract : The self‐complementary dCrGdCrGdCrG hexanucleotide, in which not only the pyrimidine/purine bases but also the ribo/deoxy sugars alternate along the sequence, was crystallized in the presence of barium cations in the form of a left‐handed Z‐type duplex. The asymmetric unit of the P 21 crystal with a pseudohexagonal lattice contains four chimeric duplexes and 16 partial Ba 2+ sites. The chimeric (DNA–RNA)2 duplexes have novel patterns of hydration and exhibit a high degree of discrete conformational disorder of their sugar‐phosphate backbones, which can at least partly be correlated with the fractional occupancies of the barium ions. The crystals of the DNA–RNA chimeric duplex in complex with Ba 2+ ions and also with Sr 2+ ions exhibit complicated twinning, which in combination with structural pseudosymmetry made structure determination difficult. The structure could be successfully solved by molecular replacement in space groups P 1 and P 21 but not in orthorhombic or higher symmetry and, after scrupulous twinning and packing analysis, was refined in space group P 21 to an R and R free of 11.36 and 16.91%, respectively, using data extending to 1.09 Å resolution. With the crystal structure having monoclinic symmetry, the sixfold crystal twinning is a combination of threefold and twofold rotations. The paper describes the practical aspects of dealing with cases of complicated twinning and pseudosymmetry, and compares the available software tools for the refinement and analysis of such cases.